A study of the effect of tungstate ions on the electrochromic properties of Ni(OH)2 films - Kotok, Valerii; Kovalenko, Vadym (Eastern-European Journal of Enterprise Technologies, 2018)
Thin films of nickel hydroxide were prepared using the cathodic template method and were tested in different electrolytes. The electrolytes were 0.1 M KOH and 0.1 M KOH with the addition of 0.1, 0.3 and 1 mM K2WO4. The test revealed, that the presence of tungstate can have a significant effect on electrochemical and electrochromic characteristics of Ni(OH)2 films. The initial sample, cycled in 0.1 M KOH showed different characteristics from those cycled in tungstate-containing electrolytes: significant difference between current densities of cathodic and anodic peaks and presence of the current plateau on the cyclic voltamperometry curve. However, the initial sample demonstrated the highest coloration degree of 74 %. On the other hand, the sample showed degradation of the coloration degree past initial growth. The samples cycled in the tungstate-containing electrolyte showed better electrochemical characteristics – sharper cathodic and anodic peaks, with the lesser difference between peak values. The dynamics of the absolute coloration degree of the samples cycled in tungstate-containing electrolyte showed a constant increase. The sample tested in a solution with 1 mM tungstate had the lowest value of the absolute coloration degree – 60 %. For tungstate concentrations of 0.1 and 0.3 mM, the absolution coloration degree at the last cycle was 72 and 71 % respectively. The samples tested in a solution with tungstate additive had a significantly lower bleaching time – 40–50 s in comparison to 360 s of the sample cycled in 0.1 М KOH. A possible mechanism that explains such differences in behavior was proposed